Diabetes in adults with intellectual disability: prevalence and associated demographic, lifestyle, independence and health factors. Issue 4 (24th January 2020) - Tyrer, F.; Ling, S.; Bhaumik, S.; Gangadharan, S. K.; Khunti, K.; Gray, L. J.; Dunkley, A. J.
Abstract: Background: As people with intellectual disabilities (ID) are now living longer, they are more at risk of developing non‐communicable diseases, including type 2 diabetes mellitus. However, understanding of factors associated with diabetes for targeted management and prevention strategies is limited. This study aimed to investigate prevalence of diabetes in adults (aged ≥18 years) with ID and its relationship with demographic, lifestyle, independence and health factors. Method: This was a cross‐sectional analysis of interview data from 1091 adults with ID from the Leicestershire Learning Disability Register from 1 January 2010 to 31 December 2016. Logistic regression models were used to identify factors associated with diabetes in the study population. Results: The study population did not have healthy lifestyles: just under half reported having lower physical activity levels than people without ID of a similar age; one‐quarter consumed fizzy drinks daily; and 20% consumed five or more fruit and/or vegetables per day. Prevalence of carer/self‐reported diabetes was 7.3% (95% confidence interval 5.9–9.0). After adjustment, diabetes was positively associated with South Asian ethnicity ( P  = 0.03) and older age groups ( P  < 0.001). Diabetes was less common in people living with family members ( P  = 0.02). We did not find a relationship between any of the lifestyle, independence and health factors investigated. Conclusions: A significant proportion of people with ID are living with diabetes. Diabetes management and prevention strategies should be tailored to individuals' complex needs and include consideration of lifestyle choices. Such strategies may want to focus on adults of South Asian ethnicity and people living in residential homes where prevalence appears to be higher.